Dangerous minds - Evanovich, Janet (New York : Bantam Books, 2017)
Buddhist monk Wayan Bagus lost his island of solitude and wants to get it back. The island was about two hundred miles northeast of Samoa. It had a mountain, beaches, a rain forest, and a volcano. And now it's gone. Poof! Vanished without a trace. Brilliant and boyishly charming Emerson Knight likes nothing better than solving an unsolvable, improbable mystery. Together with Riley Moon and his cousin, Vernon, the mismatched trio embark on a worldwide investigation that will expose a conspiracy one hundred years in the making.
Keywords: Man-woman relationships -- Fiction; Criminal investigation -- Fiction; Mystery fiction; Romantic suspense fiction; Detective and mystery fiction; Romance fiction